The development of a teacher-attitude scale for use in academic secondary schools - Ramirez, Angelina E. 1919- (s.n.], 1962)
This is a demonstration on how an attitude scale is constructed. There are two general methods that may be used in the development of attitude scales: (1) the use of a judging group and (2) the use of the direct response of agreement and disagreement with attitude statements.